2016
DOI: 10.12911/22998993/62290
|View full text |Cite
|
Sign up to set email alerts
|

Application of Cassava Peels Activated Carbon in the Treatment of Oil Refinery Wastewater – A Comparative Analysis

Abstract: Refinery wastewater most often contains hydrocarbons, spent catalyst and acid as well as soluble bases used as raw materials and treatment reagents. Most of these pollutants, which often include toxic, hazardous and priority pollutants, accounts for between 0.5-15% weight of the process wastewater [Bhatnaga and Minocha, 2009; Girish and Murty, 2013]. The need to comply with environmental regulations require that such pollutants be removed to an acceptable level

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…However, larger pore space distributions were observed on SEM microgram of ACP than on that of APP. It has been observed that numerous pore space distributions suggests high adsorption capacity [22]. On further magnification of SEM microgram of both adsorbents after simulation, the pore spaces disappeared, revealing ridges.…”
Section: Adams Bohartmentioning
confidence: 94%
See 2 more Smart Citations
“…However, larger pore space distributions were observed on SEM microgram of ACP than on that of APP. It has been observed that numerous pore space distributions suggests high adsorption capacity [22]. On further magnification of SEM microgram of both adsorbents after simulation, the pore spaces disappeared, revealing ridges.…”
Section: Adams Bohartmentioning
confidence: 94%
“…Alkyl halides, alkenes, alkynes, amino and nitro compounds were observed after adsorption as against the presence of carboxyl, hydroxyl and carbonyl groups (adsorptive sites) observed before the sorption process. It was obvious that chemical reactions of oxidation and reduction with PAH compound and displacement of certain substances took place in the course of adsorption [22]. Also, peaks at 1026.16 cm -1 and 3216.41 cm -1 representing C=O and O-H were completely absent after adsorption.…”
Section: Chemical Characteristicmentioning
confidence: 99%
See 1 more Smart Citation
“…The containers were taken out completed the 24h. Subsequently, the samples were filtered and analyzed by gas-mass chromatography to determine the remaining final oil concentrations in the water [2].…”
Section: Adsorption Tests: Kinetics and Isothermsmentioning
confidence: 99%
“…wastewater with traces of oils from washing equipment such as presses and clarifiers [1].Although these residues have been used as fuel for boilers or their mixture between the asphalt components, these measures have not been sufficient because the amounts produced of cuesco and fibrilla annually are exorbitant, and most of these are piled up and become a refuge for pests and a source of unpleasant odours at the time of decomposition [2].…”
mentioning
confidence: 99%